Estimation of environmental situation in the Republic of Belarus with various anthropogeneous load by the indicators of polymorphic markers clover creeping Trifolium repens L. - Lozinskaya, Olga V. (Journal of the Belarusian State University. Ecology, 2019)
By the ratio of phenotypes and the dynamics of variability of morphological characters in Trifolium repens L. it was shown that the greatest genetic stability is observed in populations in the places of natural landscapes. The lowest genetic stability was found in the places with heavy traffic and in the places with industrial facilities. It was determined that an increase in the number of altered genotypes under the influence of anthropogenic factors was almost doubled: 10 in natural areas and 17–23 in areas with anthropogenic load.
Keywords: antropogenic load; genetic polymorphism; clover creeping (Trifolium repens L.); elemental imbalance